Flow injection spectrophotometric determination of adrenaline using a solid-phase reactor containing triiodide ions immobilized in an anion-exchange resin - Vieira, Heberth Juliano; Fatibello-Filho, Orlando (Eclética Química, 2004)
A flow injection spectrophotometric procedure with on-line solid-phase reactor containing ion triiodide immobilized in an anion-exchange resin is proposed for the determination of adrenaline (epinephrine) in pharmaceutical products. Adrenaline is oxidized by triiodide ion immobilized in an anionic-exchange resin yielding adrenochrome which is transported by the carrier solution and detected at a wavelength of 488 nm. Adrenaline was determined in three pharmaceutical products in the 6.4 x 10 - 6 to 3.0 x 10 -4 mol L -1 concentration range with a detection limit of 4.8 x 10 -7 mol L -1 . The recovery of this analyte in three samples ranged from 96.0 to 105 %. The analytical frequency was 80 determinations per hour and the RSDs were less than 1 % for adrenaline concentrations of 6.4 x 10 -5 and 2.0 x 10 -4 mol L -1 (n=10). A paired t-test showed that all results obtained for adrenaline in commercial formulations using the proposed flow injection procedure and a spectrophotometric batch procedure agree at the 95% confidence level.